Oleuropein mediated autophagy begets antimalarial drug resistance - Sharma, Prakriti; Chaudhary, Neil Roy; Devi, Sonia; Negi, Sushmita; Tandel, Nikunj; Tyagi, Rajeev K. (Frontiers in Microbiology, 2024)
Drug resistance in Plasmodium falciparum presents a formidable challenge to the humanity.And, unavailability of an effective vaccine worsens the situation further. Autophagy is one of the mechanisms employed by parasite to evade drug pressure to survive. Autophagy induced by the P. falciparum in response to the oleuropein pressure may answer many questions related to the parasite survival as well as evolving drug tolerance. The survival/autophagy axis could be an important avenue to explore in order to address certain questions related to the evolution of drug resistance. In addition, humanized mouse model of P. falciparum infection could serve as an important preclinical tool to investigate the oleuropein-induced autophagy, potentially helping to dissect the mechanisms underlying the development of antimalarial drug resistance.